Bela Negara and Epistemic Pluralism: Negotiating Civilian and Military Knowledge in Indonesia’s Defence Transformation - M. Kemalsyah (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2025)
Indonesia’s State Defence (Bela Negara) program stands at a strategic crossroads, caught between the legacy of Total People’s Defence and the exigencies of modern hybrid warfare. This article problematizes the prevailing military epistemic monopoly within policy formulation, which systematically marginalizes civilian expertise in favor of anachronistic, territorial-physical paradigms. Utilizing a qualitative methodology grounded in the framework of Epistemic Pluralism, this study argues that contemporary national resilience requires a structured negotiation between Militerwissen (hierarchical-tactical knowledge) and Bürgerwissen (networked-civilian knowledge). The research proposes a fundamental transition toward a cognitive-technocratic defence model that prioritizes data sovereignty and intellectual capital over mere physical mobilization. Findings indicate that the functional integration of civilian expertise specifically in cyber security, epidemiology, and data science is an absolute prerequisite for defence effectiveness in the era of Gray Zone Operations. Ultimately, this shift necessitates "epistemic humility" within military institutions to foster an equitable civil-military partnership, transforming Bela Negara from a relic of civilian militarization into a dynamic instrument of modern national resilience.